How is the Elderly Minority Discursively Marginalized? A Multimodal Analysis of Ageism in The Intern (2015) - Haqikoh Ukhrowiyah (CV. Era Digital Nusantara, 2025)
Media representations significantly shape societal perceptions of aging, often marginalizing older adults within youth-centric environments. Although ageism is widely discussed in media studies, there remains a lack of research applying a systemic functional multimodal framework to examine how implicit age-based biases are discursively constructed and challenged in popular cinema. To address this gap, this study investigates how Ageism is represented both linguistically and visually in the film The Intern (2015). The objective is to uncover how age-based stereotypes and marginalization are constructed through multimodal discourse. Using a qualitative descriptive design, the study adopts Systemic Functional Linguistics (SFL) and Multimodal Discourse Analysis (MDA) as the main analytical frameworks. A total of 41 linguistic clauses and 37 visual data shots were selected from eight key scenes. The analysis of the linguistic data focused on transitivity and mood, while the visual data were interpreted using Kress and van Leeuwen’s visual grammar. Findings show that material, relational, and mental processes are dominant in representing Ageism, with younger characters often positioned as active agents and the elderly as passive or outdated figures. Declarative and interrogative moods reveal implicit judgments and doubts toward older individuals. Visually, Ageism is represented through marginal framing, color contrast, and symbolic positioning that reinforces social distance. While the film initially depicts ageist perspectives, it gradually subverts them by portraying the elderly character as competent, valuable, and eventually accepted in a modern workplace. This study is limited to selected scenes and does not include other semiotic elements such as background music or paralinguistic features. Future research could expand the scope by incorporating these aspects. In conclusion, the film offers both a critique and a reinforcement of ageist ideologies, inviting reflection on how older individuals are perceived and valued in contemporary media and workplace culture.